2006
DOI: 10.1002/ijc.22446
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for endometrial cancer in hereditary nonpolyposis colorectal cancer syndrome

Abstract: The estimated lifetime risk for endometrial carcinoma (EC) in hereditary nonpolyposis colorectal cancer syndrome (HNPCC) is 32-60%, thus supporting surveillance. The survival rate of EC patients is, however, favourable questioning the need for surveillance. Yet, the effectiveness of gynecological surveillance remains to be shown. The 2 previously published studies were based on transvaginal ultrasound (TVUS) alone. Intrauterine biopsy has not been tested in surveillance for EC in HNPCC families. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
197
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(206 citation statements)
references
References 21 publications
2
197
2
5
Order By: Relevance
“…31,32 However, according to a Finnish population-based study, screening with endometrial biopsy identified more cases of early endometrial cancer or hyperplasia compared with symptoms alone. 33 Assuming that screening has imperfect specificity, it will lead to surgery on the basis of false-positive results (ie, atypical endometrial hyperplasia in the absence of endometrial cancer on final pathology or elevated CA 125 and pelvic mass in the absence of ovarian cancer) and thereby decrease the total number of cancer cases. Consequently, the highest net health benefit in this population is achieved with a combination of annual screening from age 30 years until prophylactic surgery at age 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, according to a Finnish population-based study, screening with endometrial biopsy identified more cases of early endometrial cancer or hyperplasia compared with symptoms alone. 33 Assuming that screening has imperfect specificity, it will lead to surgery on the basis of false-positive results (ie, atypical endometrial hyperplasia in the absence of endometrial cancer on final pathology or elevated CA 125 and pelvic mass in the absence of ovarian cancer) and thereby decrease the total number of cancer cases. Consequently, the highest net health benefit in this population is achieved with a combination of annual screening from age 30 years until prophylactic surgery at age 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Die Stadienverteilung und damit auch Prognose HNPCC-assoziierter kolorektaler Karzinome, die im Rahmen eines Vorsorgeprogrammes entdeckt werden, ist signifikant günstiger verglichen zu Karzinomen, die aufgrund von Symptomen der Erkrankung diagnostiziert worden sind [277]. Die Koloskopie kann als Chromoendoskopie erfolgen.…”
Section: Level Of Evidence 2bunclassified
“…In contrast, a Finnish study showed that the use of endometrial biopsy and transvaginal ultrasound together detected EC better than transvaginal ultrasound alone. Eleven of 14 ECs were diagnosed via endometrial biopsy, compared with 8 of 14 ECs diagnosed via ultrasound alone (55 ). Because many early-stage ECs present with such symptoms as abnormal vaginal bleeding, however, it is still not clear whether heightened surveillance ultimately improves cancer detection and survival (56 ).…”
Section: Preventive Screeningmentioning
confidence: 99%